E-Commerce Platform: Free Shipping Promotion Moderation on Customer Satisfaction - Humairoh, Humairoh; Annas, Mohammad (Green Publisher, 2023)
The reason for this observation is to partly and concurrently decide the impact of service quality on customer satisfaction in Tangerang city and the variable of free shipping promotion as a moderator variable of service quality on customer satisfaction. Pattern length changed into determining the usage of a purposive sampling technique with a minimum of 96 respondents. The lowest population for this has an observed is her Shoppe customers in Tangerang city, who take gain of free shipping on their Shopee purchases. This observation is an associative causal test. Data collection equipment is inside the shape of digital surveys distributed thru Google forms. Data analysis techniques use of the JASP 0.16.4 software program. The exceptional service results had a massive advantageous effect on client satisfaction with a t-statistic of 6,610, and the free shipping marketing campaign promotion had a good-sized impact on customer satisfaction with a t-statistic of 2,083 from the high-quality carrier survey and free delivery promotion impact. Make an incredibly significant impact. The F-test result is 72,936, which significantly positively affects customer satisfaction. A Sobel looks at the rating of 2.027 > 1.986, indicating that the free delivery advertising variable moderate’s quality of service variables related to customer satisfaction. The results with a coefficient of determination of 0.601 suggest that distinct Shopee promotions on free shipping and provider quality can explain 60.1% of his Shopee customer satisfaction in Tangerang city.